Enviromental Health Risk Assessment of Diesel Particulate Matter (DPM) in Underground Mining - Muhammmad Adam Ardiansyah (JURNAL KESEHATAN LINGKUNGAN, 2019)
Workers underground mines are at risk of Diesel Particulate Matter (DPM) exposure. Exposure from DPM is one of the problems that can be found in underground mines. DPM has both carcinogenic effects and non-carcinogenic effects on humans. Due to the effects of DPM exposure, especially non-carcinogenic impacts, it is necessary to assess the risk of DPM exposure in underground mines. The Environmental Health Risk Analysis is an assessment of the health risks that can occur at any time in a population at risk. EHRA will generate quantitative risk characteristics, risk management options and communication strategies that will be applied to minimize the risk from DPM exposure. This study was conducted by looking at DPM measurement data in 4 underground mine, then calculated quantitatively by using default. Results from DPM measurements in 4 underground mines showed that DPM levels in all underground mines exceeded the threshold value of 160 Î¼g/m3, while the mean of all DPM measurements in the underground mine is 0.374 Î¼g/m3. To determine whether there are non-carcinogenic effects in DPM exposure, it can be seen by calculating RQ (Risk Quotient). The conclusion of this study indicate that in all underground mines having RQ> 1 then there is a need for risk management. In the implementation of risk management there are several ways, reduce the concentration of exposure (Csafe) and reduce exposure time. Risk communication by performing the role of each relevant part from stakeholders to workers exposed to DPM.